Numerical analysis of flow distribution behavior in a proton exchange membrane fuel cell. Issue 10 (October 2018) - Lim, B.H.; Majlan, E.H.; Daud, W.R.W.; Rosli, M.I.; Husaini, T.
Abstract: The flow distribution of a proton exchange membrane fuel cell within a manifold plays an important role on its performance. This study presents a numerical analysis of the flow distribution behavior within different manifold configurations. A two-dimensional model with 75 cells was employed to study the flow behavior. The variation in the stoichiometry and number of cells was also studied. Three different flow configurations were considered with different numbers of flow inlets and outlets. The flow characteristics, such as the pressure and velocity variations in the manifold and cells, were measured to determine the effects of the different flow configurations. The results indicated that the double inlet/outlet configuration had the best flow distribution when using 75 cells. Moreover, increasing the stoichiometry resulted in a better flow distribution to the cells in a stack.